Republic of South Sudan : The Rapid Water Sector Needs Assessment and a Way Forward - Fernando, Nihal; Garvey, Walter (World Bank, Washington, DC, 2013)
The aim of the rapid assessment is to support the transition from emergency post conflict recovery to a development approach. The completion of the water, sanitation, and hygiene, or WASH strategic framework in 2011 was intended to mark the beginning of this transition in the water resources sector. Among other things, the transition involved the adjustment of policy and strategy and possibly a rethinking of approaches as the government shifts from primarily supply-driven emergency and recovery assistance to sustainable development. This assessment is based on a review of the typology of water uses in South Sudan (chapter three) including rain-fed and irrigated agriculture, livestock, fisheries, hydropower energy production, urban and rural domestic water supply and the environment; the government's water sector program priorities (chapter four); water sector institutional and policy environment (chapter five); and issues and lessons learned from the completed and ongoing activities since 2007. This assessment framework has provided useful insights and findings and outcomes that enabled the identification of programmatic priorities and related activities that the water sector agencies may undertake with the assistance from development partners in the short and medium term. Chapters six, seven, and eight present these findings in detail.